PENGARUH JOB RESOURCES DAN JOB DEMAND TERHADAP JOB CRAFTING PERAWAT BERBASIS ETNIK DI RSUD PALAGIMATA KOTA BAUBAU: THE INFLUENCE OF JOB RESOURCES AND JOB DEMAND ON JOB CRAFTING OF ETHNIC-BASED NURSES AT RSUD PALAGIMATA BAUBAU CITY - Zaru, Zelyn Rizkiyah; Rusydi, Arni Rizqiani; Sumiaty, Sumiaty (Postgraduate Program in Public Health, Universitas Muslim Indonesia, 2024)
Abstract Background: Job crafting is affected by Job demand (JD) and Job resources (JR). Characteristics work nurse can potential give rise to fatigue And tension Because must serve service on sick man. Objective study this is for know influence of job resources And job demands to job crafting. Aim: This study aims to analyze the influence of Job Resources and Job Demand on Job Crafting of ethnic-based nurses at Palagimata Regional Hospital, Baubau City. Method: Type study this is observational with design cross-sectional study. Population study This as many as 220 and sample as many as 220 techniques taking sample based on amount population with method total sampling. Collected data analyzed with use test multiple linear regression. Results: Results study that part big respondents, manifold sex women (82 .5 %),. Results analysis multiple linear regression show all variable There is its influence to job crafting. By Partial show There is influence job demand (p=0.001) and jobs resources (p=0.000) against job crafting . Variable job demands And jod resources in a way simultaneous influential to interest buy repeat (F=0.000). Coefficient resulting determination by 57%. The most influential variable is job resources. Conclusion: Conclusion that most dominant factor influence job crafting is job resources. Recommended to the Palagimata Regional Hospital, Baubau City For more notice work the nurse.